2023
DOI: 10.18196/pt.v11i1.13628
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response, Growth, and Yield of Edamame Soybean (Glycine Max L. Merr.) Under Foliar Application of Nano Cattle Bone Ash in Entisol

Abstract: Nano cattle bone ash can reduce requirement for SP-36 and increase pod yield. This study aimed to examine the physiological response, growth, and yield of edamame soybean in entisol of concentration and frequency of foliar application of nano cattle bone ash and SP-36 fertilizer.The research was conducted an experimental method which arranged in a Randomized Completely Block Design (RCBD) which consists of factor concentration (0.15, 0.30, and 0.45%) and frequency (2, 3, and 4 times). In control treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…These results align with the research conducted by Załuszniewska & Nogalska (2022), where the application of meat and bone provided better results for winter oilseed rape and winter wheat compared to commercial NPK fertilizers. Another study conducted by Maulidayanti et al (2023) on edamame soybeans demonstrated that the application of nano bone ash at a concentration of 0.15% and a frequency of 3 times was able to substitute up to 50% of the requirement for SP36 fertilizer. This study's results align with Genesiska et al (2022), who reported that foliar application of various concentrations of chicken bone ash nano phosphate fertilizer and SP-36 had the same effects on the fresh weight and dry weight of shoots of soybean plants.…”
Section: Plant Growthmentioning
confidence: 99%
“…These results align with the research conducted by Załuszniewska & Nogalska (2022), where the application of meat and bone provided better results for winter oilseed rape and winter wheat compared to commercial NPK fertilizers. Another study conducted by Maulidayanti et al (2023) on edamame soybeans demonstrated that the application of nano bone ash at a concentration of 0.15% and a frequency of 3 times was able to substitute up to 50% of the requirement for SP36 fertilizer. This study's results align with Genesiska et al (2022), who reported that foliar application of various concentrations of chicken bone ash nano phosphate fertilizer and SP-36 had the same effects on the fresh weight and dry weight of shoots of soybean plants.…”
Section: Plant Growthmentioning
confidence: 99%